EFFECT OF PLANTING DATES AND NITROGEN LEVELS ON GREEN FORAGE YIELD OF GUINEA GRASS،GROWTH - Abdul Wahid, Mohammed Abdul-Raza; Al-Rifa'i, Shaimaa Ibrahim (Diyala Agricultural Sciences Journal, 2020)
The experiment carried out in Al- Muthanna University research station (800 m away from Samawah City Center) during the summer seasons 2017-2018 and 2018-2019 to study the effect of three planting dates (5thApril, 20thApril and 5 thMay) and five levels of nitrogen fertilization 0, 100, 150, 200 and 250 kg N ha-1 and their interaction on growth ,green forage yield of guinea Panicum maximum cv.Mombasa .Ten cutting managements were taken .The experiment was designed in a randomized complete blocks (RCBD), in a Factorial experiments with three replications .The results showed that sowing dates on 5th April gave the highest mean of plant height 137.0, 137.0, 137.9, 128.5 cm for the 1st, 6th, 7th,8th cuts respectively, green forage yield 29.1, 23.1,47.1, 43.7, 65.9, 64.9 t ha-1 for the 1st , 7nd, 3rd, 4th, 6th, 7th, 8th cuts respectively, total green forage yield 462.4 t ha-1 ,. The results showed a significant superiority in the level of fertilizer 758 kg N ha-1 on plant height 155.7,149,2,145.3 139.0,126.7 cm for the 3nd, 4th,5th, 6th,7th,10th cuts respectively, green forage yield 27.7, 57.2 ,69.3, 75.6, 67.6, 61.3 t ha-1 for the 1st , 5 th, 6th, 7th, 8th, 9th cuts respectively, total green forage yield 480.7 t ha-1 ,While the level 708 kg N ha-1 was superior in plant height 143.90,144.80,135.50,133.10 cm for the 1st, 2nd,8th, 9th cuts respectively ,green forage yield 23.10,43.30 t ha-1 for the 2nd,4th, cuts respectively.